Immunomodulatory Effects of Pure Cylindrospermopsin in Rats Orally Exposed for 28 Days - Leticia Diez-Quijada; Antonio Casas-Rodriguez; Remedios Guzmán-Guillén; Verónica Molina-Hernández; Rafael G. Albaladejo; Ana María Cameán; Angeles Jos (Toxins, 2022)
Cylindrospermopsin (CYN) is a ubiquitous cyanotoxin showing increasing incidence worldwide. CYN has been classified as a cytotoxin and, among its toxic effects, its immunotoxicity is scarcely studied. This work investigates for the first time the influence of oral CYN exposure (18.75; 37.5 and 75 µg/kg b.w./day, for 28 days) on the mRNA expression of selected interleukin (IL) genes (IL-1β, IL-2, IL-6, Tumor Necrosis Factor alpha (TNF-α), Interferon gamma (IFN-γ)) in the thymus and the spleen of male and female rats, by quantitative real-time polymerase chain reaction (RT-qPCR). Moreover, their serum levels were also measured by a multiplex-bead-based immunoassay, and a histopathological study was performed. CYN produced immunomodulation mainly in the thymus of rats exposed to 75 μg CYN/kg b.w./day in both sexes. However, in the spleen only IL-1β and IL-2 (males), and TNF-α and IFN-γ (females) expression was modified after CYN exposure. Only female rats exposed to 18.75 μg CYN/kg b.w./day showed a significant decrease in TNF-α serum levels. There were no significant differences in the weight or histopathology in the organs studied. Further research is needed to obtain a deeper view of the molecular mechanisms involved in CYN immunotoxicity and its consequences on long-term exposures.